AB0802 Beliefs and treatment satisfaction in patients receiving biological agents. (23rd January 2014) - Peixoto, D.; Teixeira, F.; Raposo, A.; Costa, J.; Bogas, M.; Afonso, C.; Araújo, D.
Abstract : Background: Treatment satisfaction represents an important outcome as it is related to adherence and willingness to continue treatment. Patients beliefs related to the medication (eg, about side effects and safety) also influence their satisfaction and, consequently, the treatment success. Satisfied patients are more likely to maintain a good relationship with a healthcare provider and report better health status 1 . Objectives: To evaluate the beliefs and satisfaction of our patients with inflammatory rheumatic diseases with their current biological therapies. Methods: Forty-one consecutive patients observed at our day-care unit completed an 18-item questionnaire concerning biological treatment. It included questions addressing their perceptions and satisfaction with their current treatment, information provided by their physician and about the knowledge and satisfaction regarding the cost of these therapies. The questionnaire was applied by the nurses to patients and blinded to provide anonymity. The attending physician was previously asked to record the disease state (remission/not remission) of each patient. Results: We included 26 females and 15 males, with a mean age of 47.1±11.9 years. Forty six percent of the patients had rheumatoid arthritis, 27% psoriatic arthritis, 22% ankylosing spondylitis and 5% had undifferentiated spondylarthritis. Forty six percent of the patients were treated with etanercept, 29% with adalimumab, 13% with infliximab, 7% with rituximab and 5% with tocilizumab and 85.4% of patients were in clinical remission. Regarding the information provided by their doctor about the treatment, 95% of patients were satisfied, 97.6% responded that this treatment was effective to control the disease and 100% that their quality of life improved with this medication. Concerning safety, although 82.9% considered this drug safe, 56% responded that they had to take special care about their health, 22% believed to have more health complications and 14.6% experienced some side effects. Regarding convenience, 87.8% responded that their treatment frequency was convenient but 46.6% were unsatisfied with the form of administration and 24.4% reported that their treatment form/frequency interfered with their professional life. In relation to costs of the biologic agents, 83% of patients considered that they are expensive and 98% didn't agreed with the price. However when we tried to understand if patients had a correct notion of the cost, 73% of patients responded <1000 euros (€)/month, 46% <500 €/month and 22% said <100 €/month. Conclusions: The majority of our patients were satisfied with the information provided by their doctor, considered the treatment effective in controlling the disease, reported improved in quality of life and considered them as safe drugs. In the negative perspective, we emphasize that 46.6% of patients are unsatisfied with the form of administration and 24.4% reported that it interfered with their professional life. Although most patients considered biological agents as expensive drugs, the majority underestimated their real cost, which reinforces the need for continuous education to raise the awareness of patients to avoid oversights/waste with the drug. References: DiMatteo MR, Prince LM, Taranta A. Patient's perceptions of physician's behavior: determinants of patient commitment to the therapeutic relationship. J Community Health 1979;4:280-90. Disclosure of Interest: None Declared